(untitled) (Experimental biology, 2019)
Aegopodium L. is a perennial plant of the Apiaceae family, growing in the mountainous regions of Europe, Siberia, the Caucasus, Kazakhstan and Central Asia. The genus Aegopodium L. includes seven species. Two species grow in Kazakhstan: Aegopodium podagraria L. and Aegopodium alpestre Ledeb. Goutweed (Aegopodium podagraria L.) as a medicinal plant for the treatment of podagra and rheumatism has been used since ancient times. But the biological and phytochemical characteristics of Aegopodium podagraria L. and Aegopodium alpestre Ledeb are very little studied. Our article presents the results of a comparative study of the anatomical and morphological structures of the underground organs of the two above-mentioned medicinal plants, as well as the determination of the moisture, ash and extract content of their raw materials. Plants were collected during the flowering period (in early July) 2017 in the big Almaty gorge (GPS coordinates of the initial point of the gorge: 43.136976, 76.903267. Height over sea level of 1500 – 2500 m). As a result of morphological study of underground organs of Aegopodium podagraria L. and Aegopodium alpestre Ledeb. it is revealed that the roots in the form of lobes are formed on horizontal rhizomes. On the cross section of the anatomical root of both plants diarсh. In the primary bark, as well as between the xylem rays accumulate starch grains. Biometric measurements of the root showed that, the indicators of Aegopodium podagraria L. are higher than, Aegopodium alpestre Ledeb. The humidity of underground organs of Aegopodium podagraria L. Aegopodium alpestre Ledeb. does not exceed the values of this indicator for pharmaceutical samples. The ash content of underground organs of Aegopodium podagraria l is 1.5 times lower than that of Aegopodium alpestre Ledeb., and the extractivity of both plants is high (25.37±6.91% and 28.13±4.95%, respectively). Keywords: goutweed (Aegopodium podagraria L.), Aegopodium alpestre Ledeb., medicinal plants, xylem, phloem, ash content, extractivity.